FORMATION OF A CAPABLE TERRITORIAL COMMUNITY WITHIN THE ARCHITECTURE OF THE STATE’S PUBLIC-SERVICE ACTIVITY - Antonova, Liudmyla; Zhovnirchyk, Yaroslav; Antonov, Andriy (Public Management and Policy, 2025)
The article investigates how a capable territorial community is formed within the evolving architecture of the state’s public-service activity. Building on Ukraine’s post-2014 decentralization and the shift toward a service-oriented state, the study conceptualizes community capacity as an integrated combination of managerial, financial, social, legal, and innovation-digital potentials that collectively enable sustainable local development and citizen-centered governance. The argument proceeds from three premises: first, decentralization is meaningful only when local authorities possess the resources and competences to deliver quality public services; second, the service state reframes the state–citizen relationship from administrative subordination to co-production and partnership; third, European integration and the digital transformation of the public sector require alignment with standards of transparency, accountability, participation, and data-driven decision-making. Methodologically, the article synthesizes public administration, economics, and sociology to propose a multidimensional framework for assessing and strengthening community capacity. Within this framework, five mutually reinforcing mechanisms are identified: (1) Financial-economic mechanisms; (2) Organizational-managerial mechanisms; (3) Human-resource mechanisms; (4) Innovation-digital mechanisms; (5) Social-capital mechanisms. The findings demonstrate that these mechanisms operate most effectively as a system, not as isolated reforms. When combined, they generate a virtuous cycle in which transparent finance supports credible planning; skilled personnel implement digital solutions; and higher civic trust widens participation, which in turn strengthens accountability and service quality. Framed by European standards of local self-government and public value, the capable community emerges as a co-equal partner of the state: it co-designs policies, co-produces services, and co-manages development risks while sustaining democratic legitimacy at the local level. The article concludes that advancing the service-state model in Ukraine depends on embedding the above mechanisms in a coherent governance architecture that privileges openness, responsibility, and measurable results. This systems approach aligns local development with EU-oriented requirements of sustainability, inclusion, and digital maturity, and provides a practical roadmap for transforming administratively created communities into genuinely capable ones that are resilient, innovation-ready, and citizen-centric.